Hubungan Kecanduan Game dengan Motivasi Belajar Siswa dan Implikasinya Terhadap Bimbingan dan Konseling - Jannah, Nurul; Mudjiran, Mudjiran; Nirwana, Herman (Konselor, 2015)
The research purpose to: (1) describe the game addiction on the student, (2) describe the student motivation, (3) find out the correlation between game addiction with student motivation. The research methodology was quantitative approach to the type of descriptive correlational. The research population was 739 students of SMP N 25 Padang academic year 2013/2014. The research sample was 266 students selected by stratified random sampling technique. The instrument used was a questionnaire with a reliability of 0.870 (game addiction) and 0.861 (learn motivation). Data were analyzed using descriptive statistical techniques and Product Moment Correlation. The research results showed that: (1) game addiction students in general are at the high category, (2) learn motivation students in general are at a high enough category, (3) there is a significant negative correlation between game addiction with students motivation, with a correlation coefficient of -0.301. Implications in guidance and counseling will discussed.